Anterolateral thigh mega flap for upper limb reconstruction: a case report - Riera, Ricardo F.; Vitelly, Juan A. U.; Azcue, Arsenio F. A.; Cacique, Mauricio D. (International Journal of Research in Medical Sciences, 2024)
The innovative concept of employing "Megaflaps", large free flaps, in particular the anterolateral thigh megaflap, for the reconstruction of large surface defects remains relatively unexplored. Although the theoretical value of "megaflaps" is recognized, their documentation remains limited. Microsurgical free flaps are essential for treating musculotendinous, osseous, and vasculonervous injuries. The appeal of these flaps lies in their minimal donor site morbidity, which offers an alternative approach. Taking advantage of the intricate anatomy of the lateral femoral circumflex artery and its branches facilitates the creation of large surface area flaps.